Environmental drivers of raccoon (Procyon lotor L.) occurrences in Austria – established versus newly invaded regions - Duscher, Tanja; Zeveloff, Samuel I.; Michler, Frank-Uwe; Nopp-Mayr, Ursula (Archives of Biological Sciences, 2018)
As we are faced with the imminent spread of the raccoon (Procyon lotor L.), a successful and highly adaptable invader in Europe, it is necessary to identify the drivers of its distribution and focal areas of its future management. Being an omnivorous species, raccoons can exert considerable influence on prey species of various taxa. Species distribution models for this invasive species can be useful tools for its management. Using a presence-only model (MaxEnt) based on environmental variables selected by raccoon experts, the presence of raccoons in Austria was predicted. Core areas of raccoon colonization are mainly located in and around cities and river valleys. Identified ecological drivers of raccoon distribution comprise climate and land-cover variables, with temperature parameters (e.g. the number of hot days, mean January temperature), the proportion of coniferous forests, settlements and elevation mainly influencing the model output. The importance of habitat parameters changes with the stage of invasion. In Austria’s established regions, the probability of raccoon presence was best predicted by variables chosen by an expert of the raccoon’s native range, while the predictors chosen by an expert in its introduced range better reflected the situation in recently invaded regions. The significance of climate and land cover in understanding the probability of raccoon presence was shown. https://doi.org/10.2298/ABS170512024D Received: May 12, 2017; Revised: June 18, 2017; Accepted: July 3, 2017; Published online: July 25, 2017 How to cite this article: Duscher T, Zeveloff SI, Michler FU, Nopp-Mayr U. Environmental drivers of raccoon (Procyon lotor L.) occurrences in Austria - established versus newly invaded regions. Arch Biol Sci. 2018;70(1):41-53.